FUNCTIONAL TECHNOLOGICAL LUBRICANTS STRUCTURIZED WITH NONFERROUS METAL NANOPOWDERS FOR EFFICIENCY UPGRADING OF TRANSPORT PART CUTTING - Gennady I. Shulga; Alexey O. Kolesnichenko; Evgeny V. Skrinnikov; Tatyana G. Shulga (Advanced Engineering Research)
Incorporation of functional water-soluble technological lubricants (FWTL) of zinc nanopowder into fractal clusters improves their greasy properties, and increases the stamping efficiency and iron plate draw-forming under the transport body parts fabrication.